Role of miRNAs in CD4 T cell plasticity during inflammation and tolerance - Sethi, Apoorva; Kulkarni, Neeraja; Sonar, Sandip; Lal, Girdhari (Frontiers in Genetics, 2013)
Gene expression is tightly regulated in a tuneable, cell-specific and time-dependent manner. Recent advancement in epigenetics and non-coding RNA revolutionized the concept of gene regulation. In order to regulate the transcription, non-coding RNA (ncRNA) can promptly response to the extracellular signals as compared to transcription factors present in the cells. microRNAs (miRNAs) are non-coding RNA (~22 bp) encoded in the genome, and present as intergenic or oriented antisense to neighboring genes. The strategic location of miRNA in coding genes helps in the coupled regulation of its expression with host genes. miRNA together with complex machinery called RNA-induced silencing complex (RISC) interacts with target mRNA and degrade the mRNA or inhibits the translation. CD4 T cells play an important role in the generation and maintenance of inflammation and tolerance. Cytokines and chemokines present in the inflamed microenvironment controls the differentiation and function of various subsets of CD4 T cells (Th1, Th2, Th17 and Tregs). Recent studies suggest that miRNAs play an important role in the development and function of all subsets of CD4 T cells. In current review, we focused on how various miRNAs are regulated by cell’s extrinsic and intrinsic signalling, and how miRNAs affect the transdifferentiation of subsets of CD4 T cell and controls their plasticity during inflammation and tolerance.